Effect of Group Mixing and Available Space on Performance, Feeding Behavior, and Fecal Microbiota Composition during the Growth Period of Pigs - Adrià Clavell-Sansalvador; Raquel Río-López; Olga González-Rodríguez; L. Jesús García-Gil; Xavier Xifró; Gustavo Zigovski; Juan Ochoteco-Asensio; Maria Ballester; Antoni Dalmau; Yuliaxis Ramayo-Caldas (Animals)
Stress significantly affects the health, welfare, and productivity of farm animals. We performed a longitudinal study to evaluate stress’s effects on pig performance, feeding behavior, and fecal microbiota composition. This study involved 64 Duroc pigs during the fattening period, divided into two experimental groups: a stress group (n = 32) and a control group (n = 32). Stressed groups had less space and were mixed twice during the experiment. We monitored body weight, feed efficiency, feeding behavior, and fecal microbiota composition. Compared to the control group, the stressed pigs exhibited reduced body weight, feed efficiency, fewer feeder visits, and longer meal durations. In the fecal microbiota, resilience was observed, with greater differences between groups when sampling was closer to the stressful stimulus. Stressed pigs showed an increase in opportunistic bacteria, such as Streptococcus, Treponema and members of the Erysipelotrichaceae family, while control pigs had more butyrate- and propionate-producing genera like Anaerobutyricum, Coprococcus and HUN007. Our findings confirm that prolonged stress negatively impacts porcine welfare, behavior, and performance, and alters their gut microbiota. Specific microorganisms identified could serve as non-invasive biomarkers for stress, potentially informing both animal welfare and similar gut-brain axis mechanisms relevant to human research.